Beginning XNA 2.0 Game Programming - Lobão, Alexandre (Apress, 2012)
According to the point-of-sale information compiled by NPD Group (http://www.NPD. com), a leading USmarketing information provider, computer and video game sales totaledmore than seven billion dollars in each of the last three years. The video game software industry is accountable formore than six billion dollars of this total. If we include portable and console hardware, software, and accessory sales, in 2006 the video game industry generated revenue of close to twelve and a half billion dollars, exceeding the previous record of around two billion dollars. By the time we completed this book—early 2008—no statistics were available yet for 2007, but there’s no expectation of lower figures. WithMicrosoft XNA, for the first time ever a nonprofessional game developer can create single andmultiplayer games that can run on both PCs and the Xbox 360 console. These figures alonemight be reason enough to interest someone in learning XNA and becoming a game developer, trying to get a share of amarket that’smore profitable than the Hollywoodmovie-making one. Although, let’s be fair and not hide the facts. Unfortunately, there are few openings in this area: about one game programming job per every thousand “real life” programming jobs.Worse than that, on average, the game industry pays its programmers less than other industries do.